Conditional Disruption of the Prolyl Hydroxylase Domain‐Containing Protein 2 (Phd2) Gene Defines Its Key Role in Skeletal Development. (October 2014) - Cheng, Shaohong; Xing, Weirong; Pourteymoor, Sheila; Mohan, Subburaman
ABSTRACT We have previously shown that the increase in osterix (Osx) expression during osteoblast maturation is dependent on the activity of the prolyl hydroxylase domain‐containing protein 2 (Phd2), a key regulator of protein levels of the hypoxia‐inducible factor family proteins in many tissues. In this study, we generated conditional Phd2 knockout mice (cKO) in osteoblast lineage cells by crossing floxed Phd2 mice with a Col1α2‐iCre line to investigate the function of Phd2 in vivo. The cKO mice developed short stature and premature death at 12 to 14 weeks of age. Bone mineral content, bone area, and bone mineral density were decreased in femurs and tibias, but not vertebrae of the cKO mice compared to WT mice. The total volume (TV), bone volume (BV), and bone volume fraction (BV/TV) in the femoral trabecular bones of cKO mice were significantly decreased. Cross‐sectional area of the femoral mid‐diaphysis was also reduced in the cKO mice. The reduced bone size and trabecular bone volume in the cKO mice were a result of impaired bone formation but not bone resorption as revealed by dynamic histomorphometric analyses. Bone marrow stromal cells derived from cKO mice formed fewer and smaller nodules when cultured with mineralization medium. Quantitative RT‐PCR and immunohistochemistry detected reduced expression of Osx, osteocalcin, and bone sialoprotein in cKO bone cells. These data indicate that Phd2 plays an important role in regulating bone formation in part by modulating expression of Osx and bone formation marker genes. © 2014 American Society for Bone and Mineral Research.